Different water environment coupled with ultraviolet radiation on ageing of asphalt binder. Issue 10 (3rd October 2021) - Qian, Guoping; Yu, Huanan; Jin, Dazhong; Bai, Xianping; Gong, Xiangbing
Abstract : Asphalt pavement is inevitably exposed to sunlight and different water environment during the service life, and the environment changes have caused the asphalt to be aged under the more complex environment such as more severe ultraviolet (UV) radiations, acid rain, or deicing salt conditions, however, the ageing mechanism and impact of coupled water and UV radiation is still not clear. In order to evaluate the coupling impact of different water environment (salt, acid) and UV radiation on the rheological properties and microstructure of asphalt material, short-term aged Rolling Thin Film Oven (RTFO) samples were further aged in UV and various water environment to simulate the UV and acid rain or salt condition, the Dynamic Shear Rheological (DSR) test, Bending Beam Rheological (BBR) test, SARA (saturates, aromatics, resin, and asphaltene) four-component analysis test and Fourier Transform Infrared Spectrometer (FTIR) tests were carried out. The results show that the coupling of different water environments and UV radiation accelerated the ageing of asphalt, which leads to the decrease of saturated, aromatic and resin content, the increase of asphaltene, and the enhancement of absorption peaks of carbonyl and sulfoxide groups. The result also found that shorter wavelength UV radiation has a severer effect on asphalt ageing under the same UV radiation level. Highlights UV and different water environment on asphalt ageing were investigated. UV and water ageing reduced the low temperature cracking resistance. UV and water ageing reduced the light component of asphalt and increased the heavy component of asphaltene. Shorter wavelength of UV have a server impact on asphalt ageing.